2019
DOI: 10.1177/0276237419897048
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Objects With Smooth or Sharp Features Created as Line Drawings by Individuals Trained in Design

Abstract: There is a long history of studies of shape preference using simple abstract twodimensional shapes. The evidence has confirmed a preference for symmetry, high contrast, and smoothness over asymmetry, low contrast, and angularity. However, the evidence about the role of culture and expertise is inconclusive. We asked a group of 56 expert designers (studying at the IUAV) to draw seven objects on paper and for each provide two versions: a smooth version and an angular version. These stimuli therefore show everyda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 51 publications
2
20
1
Order By: Relevance
“…In this study we used drawings of design products that differed on their curvature/angularity. In a previous study we had confirmed that the curved products were seen as having more positive association (Bertamini & Sinico, 2019). Here we test new tertiary associations, including the degree of perceived usefulness of these objects.…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In this study we used drawings of design products that differed on their curvature/angularity. In a previous study we had confirmed that the curved products were seen as having more positive association (Bertamini & Sinico, 2019). Here we test new tertiary associations, including the degree of perceived usefulness of these objects.…”
Section: Introductionmentioning
confidence: 75%
“…A significant link between smoothness and beauty is confirmed also by Bertamini and Sinico (2019). This study explored the effect of curvature in relation to other dimensions.…”
Section: Curvature Of Design Objectmentioning
confidence: 91%
See 2 more Smart Citations
“…The idea of a preference for smooth curvature has a long history (for a review and historical perspective see Bertamini et al, 2015). This phenomenon has been documented for a variety of visual stimuli: familiar and unfamiliar objects (Bar & Neta, 2006;Bar & Neta, 2007;Corradi et al, 2019a;Corradi et al, 2019b) geometric or irregular abstract shapes, which prevent familiarity effects (Silvia & Barona, 2009;Bertamini et al, 2015) hand-drawn objects (Bertamini & Sinico, 2021) car design (Leder & Carbon, 2005) and complex interior design environments (Vartanian et al, 2013;Banaei et al, 2017;Ruta et al, 2019). The curvature effect has been replicated across a range of tasks, including explicit forced choice responses (''like''/''no like''), rating scales (Likert scale or visual attention scales-VAS) and selection procedure where participants chose one of two stimuli presented simultaneously (Gómez-Puerto, Munar & Nadal, 2016).…”
Section: Introductionmentioning
confidence: 99%